2016
DOI: 10.1016/j.ejmech.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antitumor activity of selenium-containing quinone-based triazoles possessing two redox centres, and their mechanistic insights

Abstract: Selenium-containing quinone-based 1,2,3-triazoles were synthesized using click chemistry, the copper catalyzed azide-alkyne 1,3-dipolar cycloaddition, and evaluated against six types of cancer cell lines: HL-60 (human promyelocytic leukemia cells), HCT-116 (human colon carcinoma cells), PC3 (human prostate cells), SF295 (human glioblastoma cells), MDA-MB-435 (melanoma cells) and OVCAR-8 (human ovarian carcinoma cells). Some compounds showed IC50 values < 0.3 μM. The cytotoxic potential of the quinones evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 81 publications
1
43
0
Order By: Relevance
“…Considering the important chemical interest and potential biological applications of 1,4-naphthoquinones and chalcogen derivatives, different research groups have concentrated their efforts to develop new compounds possessing these two structural moieties [ 31 ]. A method for the synthesis of selenonaphthoquinones ( 2 ) by phenylselenide ions has been reported in the literature by Sakakibara [ 32 ], and others chalcogenium-naphthoquinones were successively explored by Jacob to obtain new redox agents ( 3-5 ) as anti-cancer drugs [ [33] , [34] , [35] , [36] ], as shown in Fig.1 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the important chemical interest and potential biological applications of 1,4-naphthoquinones and chalcogen derivatives, different research groups have concentrated their efforts to develop new compounds possessing these two structural moieties [ 31 ]. A method for the synthesis of selenonaphthoquinones ( 2 ) by phenylselenide ions has been reported in the literature by Sakakibara [ 32 ], and others chalcogenium-naphthoquinones were successively explored by Jacob to obtain new redox agents ( 3-5 ) as anti-cancer drugs [ [33] , [34] , [35] , [36] ], as shown in Fig.1 .…”
Section: Introductionmentioning
confidence: 99%
“…Dyes are also very important materials [5,6] that most quinones found themselves in [7]. They also display reach biological activities [8] like antifungal [9], antibacterial [10], anticancer [11], antimalarial [12], hypoglycemic [13], analgesic [14], anti-inflammatory [15], and HIV inhibitory [16]. The redox polymers based on quinones owing to their redox ability have been investigated to develop batteries and biosensors [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…25,26,33 Compound 6 was prepared from C-allyl lawsone upon reaction with iodine to obtain the cyclized product, which underwent nucleophilic substitution with sodium azide. Finally, the last clickable derivative 7 was obtained from nor-lapachol, previously synthesized from lapachol, by the well-established Hooker oxidation method.…”
Section: Resultsmentioning
confidence: 99%
“…24b Lapachones exhibit potent antitumor activity due to their ability to act on multiple targets, as we have recently demonstrated. 25 This family of quinoidal derivatives can be divided into α-lapachones (para-quinones) and β-lapachones (orthoquinones). We have demonstrated that both α-and β-lapachones display cytotoxic activity in cancer cells.…”
mentioning
confidence: 99%